2019
DOI: 10.1186/s12889-019-6535-5
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of physical activity on prescription with access to counsellors in routine care: a qualitative study in Sweden

Abstract: Background Physical activity on prescription (PAP) has been implemented in several countries, including Sweden, to support patients who might benefit from increased physical activity. This study explores the experiences of recipients of PAP in routine health care in Sweden that offers the recipients support from physical activity counsellors. The aim was to explore influences on engagement in physical activity by PAP recipients’ from a long-term perspective. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(54 citation statements)
references
References 34 publications
2
52
0
Order By: Relevance
“…If they were and the informants forgot about it, this suggests that the TCP prescription form itself did not have a direct impact on tobacco cessation from the patients' perspective. This is consistent with the findings from a study on patients' experiences of PAP in Sweden, showing that the PAP prescription form was forgotten by patients and mainly had a symbolic value compared to the subsequent support provided [43]. Previous studies have shown that advice may be taken more seriously when combined with a prescription form [20,43] but this was not reported by the informants in this study.…”
Section: Plos Onesupporting
confidence: 91%
“…If they were and the informants forgot about it, this suggests that the TCP prescription form itself did not have a direct impact on tobacco cessation from the patients' perspective. This is consistent with the findings from a study on patients' experiences of PAP in Sweden, showing that the PAP prescription form was forgotten by patients and mainly had a symbolic value compared to the subsequent support provided [43]. Previous studies have shown that advice may be taken more seriously when combined with a prescription form [20,43] but this was not reported by the informants in this study.…”
Section: Plos Onesupporting
confidence: 91%
“…After continuing PAP treatment for 2 years, a majority of patients in both the PT and HCC groups increased their PA level and improvements in TotalMET, BMI, HDL, and MCS over time were shown for both groups. Possibly the results would have been more pronounced if we had allowed the patients to choose the study arm, instead of randomly assigning them to the interventions as we acknowledge the importance of an individualized process for the patient [ 10 12 ]. The results should be considered in light of the fact that discontinuing PAP treatment at 6 months could risk adherence deterioration and a return to the baseline levels of PA and risk markers.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review presented high-level evidence, which showed that PAP can increase the PA level in patients being insufficiently active in the healthcare setting [ 9 ]. The individualized parts of PAP treatment may be crucial in influencing the patient’s capability and motivation to increase PA [ 10 12 ]. Swedish PAP studies have shown that, among subjects that increased their PA levels, compliance declined over time.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly two-fifths of the participants in this study took up the offer of counsellor support. Some patients may feel reluctant to seek support [ 34 ] and, therefore, it is likely that a PAP model in which patients are contacted by a counsellor leads to a higher proportion of counsellor use. For some, the reason for not utilizing the support of a physical activity counsellor might be related to factors that could be facilitated by the counsellors, such as low motivation to start physical activity [ 35 ] or insufficient self-efficacy and low expectations concerning one’s own ability to engage in physical activity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%